2019
DOI: 10.1158/0008-5472.can-18-3297
|View full text |Cite
|
Sign up to set email alerts
|

NFAT1-Mediated Regulation of NDEL1 Promotes Growth and Invasion of Glioma Stem-like Cells

Abstract: Glioma stem-like cells (GSC) promote tumor generation and progression. However, the mechanism of GSC induction or maintenance is largely unknown. We previously demonstrated that the calcium-responsive transcription factor nuclear factor of activated T cells-1 (NFAT1) is activated in glioblastomas and regulates the invasion of tumor cells. In this study, we further explored the role of NFAT1 in GSC. We found that NFAT1 expression was associated with an aggressive phenotype and predicted poor survival in gliomas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 51 publications
(78 reference statements)
0
46
0
Order By: Relevance
“…The slices were then stained with an immunohistochemical labeling kit (MaxVision Biotechnology, Fuzhou, China) and imaged under a light microscope (Olympus, Tokyo, Japan). The German immunohistochemical score (30) was used to evaluate the staining intensity and expression levels.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
See 3 more Smart Citations
“…The slices were then stained with an immunohistochemical labeling kit (MaxVision Biotechnology, Fuzhou, China) and imaged under a light microscope (Olympus, Tokyo, Japan). The German immunohistochemical score (30) was used to evaluate the staining intensity and expression levels.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…The glioma cells and GSCs treated under different conditions were seeded into 96-well plates at 1 £ 10 3 cells/well and cultured for 5 days. Cell viability was detected using the CellTiter 96 Ò Aqueous Non-Radioactive Cell Proliferation Assay Kit (Promega, Madison, WI, USA) according to the manufacturer's instructions [30].…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins enriched in the top 10 pathways interacted with DPTs of sevoflurane from DTome. Because the GABAergic synapse [28], cAMP signaling pathways [29], and calcium signaling [30] are strongly related to neurotoxicity and neurodevelopment, the genes included in these signaling pathways were selected to investigate DPT-associated genes. Interestingly, bioinformatics analysis of the candidate genes revealed that GABARAPL1 and 2 were core proteins among the DPT-associated proteins.…”
mentioning
confidence: 99%